Biomass hard carbon material and preparation method thereof, and sodium ion battery
Patent Information
- Application Number
- CN202611360820.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-20
AI Technical Summary
而传统酸洗、碱洗、溶剂预处理及直接炭化工艺仅能实现局部组分改性或浅层造孔,无法对生物质全组分进行协同解构与精准调控,不仅造成大量有效炭化组分浪费、原料利用率低,还无法同步实现炭层间距调控、闭孔构筑、杂原子原位掺杂等多重改性效果,难以从根本上优化硬炭的储钠结构,对电化学性能提升的效果有限
[0062]为更好地说明本发明的目的、技术方案和有益效果,下面将结合具体实施例对本发明作进一步说明。需说明的是,下述实施所述方法是对本发明做的进一步解释说明,不应当作为对本发明的限制。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy material preparation technology, particularly to the field of carbon material preparation technology, and even more particularly to the preparation method of biomass hard carbon material, biomass hard carbon material and sodium-ion battery. Background Technology
[0002] Sodium-ion batteries, with their advantages of abundant resources, low cost, and environmental friendliness, have broad application prospects in large-scale energy storage and low-speed power applications. Hard carbon, with its unique disordered structure, large interlayer spacing, and abundant closed pores, can accommodate the insertion, extraction, and transport of sodium ions, making it a high-potential high-quality anode material for sodium-ion batteries. Agricultural and forestry biomass wastes such as coconut shells, apricot shells, walnut shells, and palm shells are widely available and renewable, making them ideal precursors for the preparation of biomass-based hard carbon and possessing a solid foundation for industrial application.
[0003] Currently, the preparation and modification technology of biomass-based hard carbon still faces many key bottlenecks, severely limiting the industrialization of high-performance hard carbon anode materials. Specifically, there are three main drawbacks. First, traditional chemical pore-forming processes suffer from poor environmental performance, high equipment wear and tear, and easy damage to the material structure. Currently, the industry commonly uses chemical activators such as potassium hydroxide, phosphoric acid, and zinc chloride to modify the pore structure of biomass hard carbon, optimizing the material's pore structure and sodium storage capacity. However, this process has significant drawbacks: the activating reagents are highly corrosive, easily damaging production equipment and increasing preparation costs. Furthermore, the reaction generates large amounts of acidic and alkaline waste liquids and solid waste, requiring complex subsequent environmental treatment processes, which does not meet the requirements of green production. Simultaneously, strong chemical etching can excessively erode the carbon skeleton, destroying the original closed-pore structure of biomass sodium storage, causing the carbon matrix to collapse, resulting in low initial coulombic efficiency and poor cycle stability, affecting battery life. Second, existing preparation processes cannot achieve efficient utilization of all biomass components, resulting in low resource utilization. Natural biomass consists of cellulose, hemicellulose, and lignin crosslinked to form a dense lignin-carbohydrate complex (LCC). All three components can be carbonized and modified, making them valuable for applications. However, traditional acid washing, alkali washing, solvent pretreatment, and direct carbonization processes can only achieve localized component modification or shallow pore formation, failing to synergistically deconstruct and precisely control the entire biomass composition. This not only results in a significant waste of effective carbonized components and low raw material utilization, but also fails to simultaneously achieve multiple modification effects such as carbon layer spacing control, closed-pore construction, and in-situ heteroatom doping. Consequently, it is difficult to fundamentally optimize the sodium storage structure of hard carbon, limiting its effect on improving electrochemical performance. Finally, biomass hard carbon prepared by conventional processes exhibits poor intrinsic conductivity and unsatisfactory charge transport kinetics. During the direct high-temperature carbonization of biomass, pyrolysis gases escape rapidly, making it difficult to form a continuous and stable conductive network and regular pore structure. The resulting hard carbon skeleton exhibits uneven disorder, scarce conductive pathways, and chaotic defect distribution. This structural problem results in slow electron conduction rate and high sodium ion transport resistance in the material, leading to defects such as low reversible specific capacity, insufficient low-pressure sodium storage capacity, and poor rate performance, which cannot meet the industrial application requirements of high energy density and high rate sodium-ion batteries.
[0004] In summary, existing biomass-based hard carbon preparation technologies face multiple technical challenges, including environmentally unfriendly chemical processes, low utilization rate of all biomass components, poor material conductivity, and limited overall sodium storage performance. The industry urgently needs to develop a green and efficient new hard carbon preparation process that can simultaneously achieve full utilization of biomass components and structural conductivity modification in order to overcome existing technological barriers. Summary of the Invention
[0005] To address the aforementioned problems, the present invention aims to provide a biomass hard carbon material, its preparation method, and a sodium-ion battery. This preparation method fully utilizes the cellulose, hemicellulose, and lignin in biomass, and can prepare a hard carbon material with excellent conductivity and porous structure. The resulting hard carbon material exhibits superior sodium storage performance, resulting in high overall performance in sodium-ion batteries, including high capacity, cycle life, and rate capability.
[0006] To achieve the above objectives, the first aspect of the present invention provides a method for preparing biomass hard carbon material, comprising the steps of: (I) Preparation of DES1 and DES2 treatment agents The hydrogen bond acceptor and hydrogen bond donor are mixed in water, heated until the solution is clear, and then the water is removed by rotary evaporation to obtain DES1 treatment agent. The hydrogen bond acceptor is an inorganic chloride salt and the hydrogen bond donor is an organic acid. A mixture of methyltriphenylphosphine bromide, an aliphatic amide, and an alcohol is heated until the system becomes clear to obtain DES2 treatment agent; (II) Separation of biomass components The biomass powder and the DES1 treatment agent were mixed, heated and reacted, and then filtered to obtain filtrate and filter cake. (III) Filtrate treatment The filtrate is dried and then catalytically graphitized to obtain graphite, and the graphite is purified to obtain crystallized carbon. (IV) Carbonization treatment The filter cake, the DES2 treatment agent, and the crystallized carbon are mixed and carbonized, followed by further processing.
[0007] In this preparation method, biomass powder is first treated with DES1 as a heat treatment agent. The inorganic chlorides and organic acids in the DES1 treatment agent can break the β-O-4 ether bonds of lignin and the ester bonds of hemicellulose in the biomass, thereby deconstructing the cross-linked structure of the lignin-carbohydrate complex (LCC), selectively separating lignin and hemicellulose, and purifying the cellulose skeleton. The filter cake after filtration is rich in cellulose, and the filtrate contains DES1 as a treatment agent and is rich in hemicellulose and lignin. After drying, the filtrate is subjected to catalytic graphitization treatment. The inorganic chlorides it contains can catalyze the graphitization of hemicellulose and lignin to obtain crystallized carbon with improved electrical conductivity. In addition, the DES1 treatment agent, with its hydrogen bond acceptor inorganic chlorides, contains Cl... - It can compete with the hydroxyl groups in the hydrogen bond donor for hydrogen bonds inside cellulose, thereby disrupting the cellulose crystallization region, reducing crystallinity, forming loose multi-level channels, and preserving the complete long cellulose chain, so as to avoid small interlayer spacing and lack of closed pores after biomass carbonization.
[0008] Furthermore, the filter cake, DES2 treatment agent, and crystallized carbon are mixed and then carbonized. The polyphenyl rings of methyltriphenylphosphine bromide in the DES2 treatment agent are fully dispersed in the crystallized carbon through π-π interaction. The aliphatic amide forms strong hydrogen bonds with the cellulose hydroxyl groups, which can deeply penetrate and anchor the cellulose. Moreover, the gas released by the thermal decomposition of aliphatic amide and alcohol at the high temperature of carbonization has an expansion effect, which can generate nanopores in situ. Nitrogen and phosphorus elements are doped in situ to form active sites.
[0009] Therefore, the preparation method of the present invention can produce biomass-based hard carbon rich in closed pores, with large interlayer spacing, uniform dispersion of crystallized carbon, and co-doped with nitrogen / phosphorus, which has better sodium storage performance and can have high comprehensive performance such as capacity, cycle life and rate capability when used in sodium-ion batteries.
[0010] As a technical solution of the present invention, the hydrogen bond acceptor is selected from at least one of ferric chloride, cobalt chloride, nickel chloride, and copper chloride.
[0011] As a technical solution of the present invention, the hydrogen bond donor is selected from at least one of benzoic acid, p-toluenesulfonic acid, p-hydroxybenzoic acid, acrylic acid, maleic acid and citric acid.
[0012] As one technical solution of the present invention, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:1~6.
[0013] As one technical solution of the present invention, the heating temperature in the preparation of DES1 treatment agent is 50~70 ℃.
[0014] As a technical solution of the present invention, water is added to the preparation of DES1 treatment agent to aid dissolution, and the water is removed by rotary evaporation after the solution is clarified. The water content is 100-300% of the sum of the mass of the hydrogen bond acceptor and the hydrogen bond donor.
[0015] As a technical solution of the present invention, the aliphatic amide is selected from at least one of formamide, acetamide and propionamide.
[0016] As one technical solution of the present invention, the alcohol is selected from ethylene glycol and / or glycerol.
[0017] As one technical solution of the present invention, the molar ratio of the methyltriphenylphosphine bromide, the aliphatic amide and the alcohol is 1:1~3:2~5.
[0018] As one technical solution of the present invention, the heating temperature in the preparation of DES2 treatment agent is 60~90 ℃.
[0019] As one technical solution of the present invention, the mass ratio of the biomass powder to the DES1 treatment agent is 1:5~20.
[0020] As one technical solution of the present invention, the heating reaction temperature is 50~80 ℃ and the time is 2~8 h.
[0021] As one technical solution of the present invention, after the heating reaction, hot water at 50~80 ℃ is added for dilution and ultrasonic dispersion is performed before filtration. The ultrasonic dispersion frequency is 20~40 kHz and the time is 20~60 min.
[0022] As a technical solution of the present invention, the filter cake in step (II) biomass component separation is washed until neutral and dried at 75~95 °C.
[0023] As one technical solution of the present invention, the drying temperature is 75~95 ℃.
[0024] As a technical solution of the present invention, the catalytic graphitization in step (III) filtrate treatment is carried out under an inert atmosphere, wherein the inert atmosphere is selected from nitrogen, argon, helium, neon or xenon.
[0025] As a technical solution of the present invention, the temperature of catalytic graphitization in step (III) filtrate treatment is 1600~2100 ℃, the heating rate is 1~10 ℃ / min, and the time is 1~5 h.
[0026] As one technical solution of the present invention, the mass ratio of the filter cake, the DES2 treatment agent and the crystallized carbon is 1:2~10:0.01~0.06.
[0027] As a technical solution of the present invention, the carbonization in step (IV) is carried out under an inert atmosphere, wherein the inert atmosphere is selected from nitrogen, argon, helium, neon or xenon.
[0028] As a technical solution of the present invention, the post-processing includes grinding and sieving in sequence.
[0029] As one technical solution of the present invention, the biomass powder is obtained by drying, crushing and sieving fruit shells.
[0030] As one technical solution of the present invention, the fruit shell is selected from coconut shell, apricot shell, walnut shell or palm shell.
[0031] As one technical solution of the present invention, the drying temperature is 75~95 ℃ and the time is 12~24 h.
[0032] As one technical solution of the present invention, the crushing process involves first coarse crushing and then fine crushing.
[0033] As one technical solution of the present invention, the sieving is a 400-mesh sieve.
[0034] As a technical solution of the present invention, the purification process includes acid washing, water washing, and drying of the graphitized material.
[0035] As one technical solution of the present invention, the pickling solution is hydrochloric acid with a concentration of 8~12 mol / L, the mass ratio of the graphite to the hydrochloric acid is 1:4~6, and the pickling temperature is 50~80 ℃ and the time is 2~10 h.
[0036] As a technical solution of the present invention, the water washing is carried out by water filtration until the pH value of the filtrate is neutral.
[0037] As one technical solution of the present invention, the drying is performed at 75~95 °C until constant weight.
[0038] As a technical solution of the present invention, the carbonization in step (IV) carbonization process adopts a stepped heating carbonization.
[0039] As one technical solution of the present invention, the temperature is first raised to 400-700℃ at a rate of 1-10℃ / min and held for 1-5 hours, and then raised to 1200-1500℃ at a rate of 1-10℃ / min and held for 1-4 hours.
[0040] The second part of this invention provides a biomass hard carbon material prepared by the aforementioned method, having a specific surface area of 5.0~15.0 m². 2 / g;d 002 The wavelength range is 0.370–0.390 nm; the volume resistivity is 0.030–0.050 Ω·cm; I D / I G The specific gravity is 1.80~2.00; the reversible specific capacity is 300~330 mAh / g; the capacity retention rate at 5C / 0.1C is 40~60%; the capacity retention rate after 1000 cycles at 1C is 85~95%; the pore size of the closed pores is 0.4~1.8 nm, and the pore volume of the closed pores is 0.1~0.3 cm³. 3 / g. This hard carbon material has excellent sodium storage performance, making it particularly suitable as a negative electrode active material for sodium-ion batteries.
[0041] The third part of this invention provides a sodium-ion battery, including a positive electrode active material, an electrolyte, and the aforementioned biomass hard carbon material. Attached Figure Description
[0042] Figure 1 This is a schematic flowchart of the biomass hard carbon material preparation method of the present invention.
[0043] Figure 2 The images show the XRD patterns of the hard carbon materials obtained in Example 1 and Comparative Example 1. Detailed Implementation
[0044] The biomass hard carbon material of this invention can be used alone or in combination with other negative electrode active materials (such as natural graphite, silicon oxide materials, silicon carbon materials, soft carbon, and / or hard carbon). The biomass hard carbon material can be applied in secondary batteries, which include positive electrode active materials and negative electrode active materials. Positive electrode active materials may include layered oxide series sodium-ion positive electrode materials, Prussian blue (white) series sodium-ion positive electrode materials, and polyanionic compound series sodium-ion positive electrode materials.
[0045] The specific surface area of the biomass hard carbon material of this invention is 5.0~15.0 m². 2 / g, as an example, can be, but is not limited to, 5.0 m 2 / g, 6.0 m 2 / g, 7.0 m 2 / g、8.0 m 2 / g, 9.0 m 2 / g, 10.0 m 2 / g, 11.0 m 2 / g, 12.0 m 2 / g, 13.0 m 2 / g, 14.0 m 2 / g, 15.0 m 2 / g. d 002 The wavelength is 0.370~0.390 nm. For example, d... 002 The nm depth can be, but is not limited to, 0.370 nm, 0.375 nm, 0.380 nm, 0.385 nm, and 0.390 nm. The volume resistivity is 0.030~0.050 Ω·cm, and for example, it can be, but is not limited to, 0.030 Ω·cm, 0.035 Ω·cm, 0.040 Ω·cm, 0.045 Ω·cm, and 0.050 Ω·cm. D / I G The value is 1.80~2.00, for example, I. D / I GPossible values include, but are not limited to, 1.80, 1.85, 1.90, 1.95, and 2.00. The reversible specific capacity is 300~330 mAh / g, and for example, it includes, but is not limited to, 300 mAh / g, 305 mAh / g, 310 mAh / g, 315 mAh / g, 320 mAh / g, 325 mAh / g, and 330 mAh / g. The capacity retention rate at 5C / 0.1C is 40~60%, and for example, it includes, but is not limited to, 40%, 45%, 50%, 55%, and 60%. The capacity retention rate after 1000 cycles at 1C is 85~95%, and for example, it includes, but is not limited to, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, and 95%. The pore size of the closed pores is 0.4~1.8 nm, and the pore volume is 0.1~0.3 cm³. 3 / g, as an example, the pore size of the closed pores can be, but is not limited to, 0.4 nm, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1.0 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, and 1.8 nm, and the pore volume of the closed pores can be, but is not limited to, 0.1 cm³. 3 / g, 0.15 cm 3 / g, 0.2 cm 3 / g, 0.25 cm 3 / g, 0.3 cm 3 / g.
[0046] The preparation method of the biomass hard carbon material of the present invention includes the following steps.
[0047] (I) Preparation of DES1 and DES2 treatment agents The hydrogen bond acceptor and hydrogen bond donor are mixed in water, heated until the solution is clear, and then the water is removed by rotary evaporation to obtain DES1 treatment agent. The hydrogen bond acceptor is an inorganic chloride salt and the hydrogen bond donor is an organic acid.
[0048] A mixture of methyltriphenylphosphine bromide, an aliphatic amide, and an alcohol is heated until the system becomes clear to obtain the DES2 treatment agent.
[0049] (II) Separation of biomass components The biomass powder and DES1 treatment agent were mixed, heated, and then filtered to obtain filtrate and filter cake.
[0050] (III) Filtrate treatment The filtrate was dried and then catalytically graphitized to obtain graphitized material. The graphitized material was then purified to obtain crystallized carbon.
[0051] (IV) Carbonization treatment The filter cake, DES2 treatment agent, and crystallized carbon are mixed and carbonized, followed by post-treatment.
[0052] The preparation method is as follows: Figure 1 As shown, biomass rich in cellulose, hemicellulose, and lignin can be separated into two parts through shearing and extraction under the action of DES1 treatment agent. The first part is rich in cellulose, and the second part is rich in hemicellulose, lignin, and DES1 treatment agent. The carbon source in the second part is graphitized under the catalytic action of DES1 treatment agent to obtain crystallized carbon. The first part, crystallized carbon, and DES2 treatment agent are carbonized together to produce biomass hard carbon material.
[0053] In step (I), during the preparation of the DES1 treatment agent, the hydrogen bond acceptor is selected from at least one of ferric chloride, cobalt chloride, nickel chloride, and copper chloride. The hydrogen bond donor is selected from at least one of benzoic acid, p-toluenesulfonic acid, p-hydroxybenzoic acid, acrylic acid, maleic acid, and citric acid. The molar ratio of hydrogen bond acceptor to hydrogen bond donor is 1:1 to 6; for example, the molar ratio may be, but is not limited to, 1:1, 1:2, 1:3, 1:4, 1:5, or 1:6. The heating temperature is 50 to 70 °C; for example, the temperature may be, but is not limited to, 50 °C, 53 °C, 55 °C, 58 °C, 60 °C, 63 °C, 65 °C, 67 °C, or 70 °C. To aid solubility, additional water may be added and the solution may be removed by rotary evaporation after clarification. The water content shall be 100% to 300% of the sum of the masses of the hydrogen bond acceptors and hydrogen bond donors. For example, the water content may be, but is not limited to, 100%, 150%, 200%, 250%, or 300%.
[0054] In step (I) of preparing the DES2 treatment agent, the aliphatic amide is selected from at least one of formamide, acetamide, and propionamide. The alcohol is selected from ethylene glycol and / or glycerol. The molar ratio of methyltriphenylphosphine bromide, the aliphatic amide, and the alcohol is 1:1 to 3:2 to 5. For example, the molar ratio may be, but is not limited to, 1:1:2, 1:1:3, 1:1:4, 1:1:5, 1:2:2, 1:2:3, 1:2:4, 1:2:5, 1:3:2, 1:3:3, 1:3:4, and 1:3:5. The heating temperature is 60 to 90 °C. For example, the temperature may be, but is not limited to, 60 °C, 63 °C, 65 °C, 68 °C, 70 °C, 73 °C, 75 °C, 77 °C, 80 °C, 83 °C, 85 °C, 87 °C, and 90 °C.
[0055] In step (II) of biomass component separation, the biomass powder is obtained by drying, crushing, and sieving fruit shells. The fruit shells are selected from coconut shells, apricot shells, walnut shells, or palm shells. The drying temperature is 75–95 °C, and the time is 12–24 h; for example, the temperature can be, but is not limited to, 75 °C, 80 °C, 85 °C, 90 °C, or 95 °C. Crushing involves first coarse crushing followed by fine crushing. Sieving is performed through a 400-mesh sieve.
[0056] The mass ratio of biomass powder to DES1 treatment agent is 1:5 to 20. For example, the mass ratio may be, but is not limited to, 1:5, 1:7, 1:9, 1:10, 1:12, 1:14, 1:16, 1:18, or 1:20. The heating temperature is 50 to 80 °C, and the time is 2 to 8 h. For example, the temperature may be, but is not limited to, 50 °C, 55 °C, 60 °C, 65 °C, 70 °C, 75 °C, or 80 °C, and the time may be, but is not limited to, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, or 8 h.
[0057] After heating and reaction, the mixture is diluted with hot water at 50–80 °C, ultrasonically dispersed, and then filtered. The ultrasonic dispersion frequency is 20–40 kHz, and the time is 20–60 min. The temperature of the hot water can be, but is not limited to, 50 °C, 55 °C, 60 °C, 65 °C, 70 °C, 75 °C, or 80 °C. The filter cake is first washed until neutral, and then dried at 75–95 °C to constant weight. For example, the drying temperature can be, but is not limited to, 75 °C, 80 °C, 85 °C, 90 °C, or 95 °C.
[0058] In step (III) filtrate treatment, the filtrate is dried at a temperature of 75~95 °C. For example, the drying temperature may be, but is not limited to, 75 °C, 80 °C, 85 °C, 90 °C, or 95 °C. Catalytic graphitization is carried out under an inert atmosphere, which may be selected from nitrogen, argon, helium, neon, or xenon. The temperature for catalytic graphitization is 1600~2100 ℃, the heating rate is 1~10 ℃ / min, and the time is 1~5 h. For example, the temperature for catalytic graphitization can be, but is not limited to, 1600 ℃, 1650 ℃, 1700 ℃, 1750 ℃, 1800 ℃, 1850 ℃, 1900 ℃, 1950 ℃, 2000 ℃, 2050 ℃, 2100 ℃, the heating rate can be, but is not limited to, 1 ℃ / min, 2 ℃ / min, 3 ℃ / min, 4 ℃ / min, 5 ℃ / min, 6 ℃ / min, 7 ℃ / min, 8 ℃ / min, 9 ℃ / min, 10 ℃ / min, and the time can be, but is not limited to, 1 h, 2 h, 3 h, 4 h, 5 h.
[0059] The purification process includes acid washing, water washing, and drying of the graphite. The acid washing solution used is hydrochloric acid with a concentration of 8–12 mol / L. For example, the concentration of hydrochloric acid may be, but is not limited to, 8.0 mol / L, 8.5 mol / L, 9.0 mol / L, 9.5 mol / L, 10.0 mol / L, 10.5 mol / L, 11.0 mol / L, 11.5 mol / L, or 12.0 mol / L. The mass ratio of graphite to hydrochloric acid is 1:4–6. For example, the mass ratio may be, but is not limited to, 1:4, 1:5, or 1:6. The pickling temperature is 50–80 °C and the time is 2–10 h. For example, the temperature can be, but is not limited to, 50 °C, 55 °C, 60 °C, 65 °C, 70 °C, 75 °C, or 80 °C, and the time can be, but is not limited to, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or 10 h. Of course, other acids besides hydrochloric acid can also be used to pickle the graphitized material to remove impurities. Water washing is performed by water filtration until the pH of the filtrate is neutral. Drying is performed at 75–95 °C to constant weight. For example, the drying temperature can be, but is not limited to, 75 °C, 80 °C, 85 °C, 90 °C, or 95 °C.
[0060] In step (IV) carbonization, the mass ratio of filter cake, DES2 treatment agent, and crystallized carbon is 1:2~10:0.01~0.06. For example, the mass ratio of the three can be, but is not limited to, 1:2:0.01, 1:2:0.03, 1:2:0.05, 1:2:0.06, 1:4:0.01, 1:4:0.02, 1:4:0.07, 1:4:0.09, 1:6:0.01, 1:6:0.03, 1:6:0.05, 1:6:0.06, 1:8:0.01, 1:8:0.04, 1:8:0.05, 1:8:0.06, 1:10:0.01, 1:10:0.04, 1:10:0.05, and 1:10:0.06. Post-processing includes sequential grinding and sieving.
[0061] Carbonization is carried out under an inert atmosphere, selected from nitrogen, argon, helium, neon, or xenon. A stepped heating method is used. First, the temperature is increased to 400–700 °C at a rate of 1–10 °C / min and held for 1–5 h, then increased to 1200–1500 °C at a rate of 1–10 °C / min and held for 1–4 h. For example, the heating rate may be, but is not limited to, 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, 5 °C / min, 6 °C / min, 7 °C / min, 8 °C / min, 9 °C / min, or 10 °C / min. The carbonization temperature for the first stage can be, but is not limited to, 400 ℃, 450 ℃, 500 ℃, 550 ℃, 600 ℃, 650 ℃, or 700 ℃, and the holding time can be, but is not limited to, 1 h, 2 h, 3 h, 4 h, or 5 h. The carbonization temperature for the second stage can be, but is not limited to, 1200 ℃, 1250 ℃, 1300 ℃, 1350 ℃, 1400 ℃, 1450 ℃, or 1500 ℃, and the holding time can be, but is not limited to, 1 h, 2 h, 3 h, or 4 h.
[0062] To better illustrate the purpose, technical solution, and beneficial effects of this invention, the invention will be further described below with reference to specific embodiments. It should be noted that the methods described below are further explanations of this invention and should not be construed as limiting it.
[0063] Example 1 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.
[0064] (I) Preparation of DES1 and DES2 treatment agents Ferric chloride and benzoic acid were added to a container at a molar ratio of 1:1. Water (containing 100% of the sum of the masses of ferric chloride and benzoic acid) was added and the mixture was stirred at 50 °C until clear. The solution was then rotary evaporated to remove free water, yielding the DES1 treatment agent.
[0065] Methyltriphenylphosphine bromide, formamide, and ethylene glycol were added to a container in a molar ratio of 1:1:2 and stirred continuously at 60 °C until clear to obtain DES2 treatment agent.
[0066] (II) Separation of biomass components Coconut shells were dried at 95 °C for 12 h, crushed, pulverized, and passed through a 400-mesh sieve to obtain coconut shell powder. The coconut shell powder and DES1 treatment agent were added to a container at a mass ratio of 1:5 and stirred at 60 °C for 7 h. Then, pure water at 60 °C was added for dilution, and the mixture was ultrasonically dispersed at a frequency of 20 kHz for 60 min. After filtration, the mixture was continuously washed with pure water at 60 °C until the filtrate was neutral. The filter cake was then placed in a constant temperature oven at 85 °C and dried to constant weight.
[0067] (III) Filtrate treatment The filtrate was dried to constant weight in an oven at 85 °C and placed in a kiln filled with nitrogen atmosphere. The temperature was increased to 1600 °C at a rate of 5 °C / min and held for 5 h to obtain graphitization. After cooling to room temperature, the graphitization and hydrochloric acid (concentration of 8 mol / L) were mixed at a mass ratio of 1:6 and reacted at 60 °C for 6 h. The mixture was then washed with water and filtered until the pH of the filtrate was neutral. The filter cake was then dried to constant weight in an oven at 85 °C to obtain crystallized carbon.
[0068] (IV) Carbonization treatment The filter cake, DES2 treatment agent, and crystallized carbon from step (II) biomass component separation were mixed evenly at a mass ratio of 1:2:0.01. The mixture was then placed in a tube furnace filled with nitrogen and heated to 500 °C at a rate of 5 °C / min, held for 4 h, and then further heated to 1200 °C at a rate of 5 °C / min and held for 2 h. After cooling to room temperature, the mixture was ground through a 400-sieve to obtain biomass hard carbon material.
[0069] The prepared biomass hard carbon material was subjected to XRD testing, and the results are as follows: Figure 2 As shown, by Figure 2 The XRD results of the neutralization and comparison with those of Comparative Example 1 show that the prepared biomass hard carbon material has sharp peaks near 26.5° and 54.5°, which correspond to the 002 and 004 characteristic peaks of graphite, indicating that it contains crystallized carbon and the content exceeds the detection limit (5 wt.%).
[0070] Example 2 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.
[0071] (I) Preparation of DES1 and DES2 treatment agents Cobalt chloride and p-toluenesulfonic acid were added to a container at a molar ratio of 1:2. Water (containing 200% of the sum of the masses of cobalt chloride and p-toluenesulfonic acid) was added and the mixture was stirred at 60 °C until clear. The solution was then rotary evaporated to remove free water, yielding the DES1 treatment agent.
[0072] Methyltriphenylphosphine bromide, acetamide, and glycerol were added to a container in a molar ratio of 1:2:3 and stirred continuously at 70 °C until clear to obtain DES2 treatment agent.
[0073] (II) Separation of biomass components Apricot shells were dried at 85 °C for 18 h, crushed, pulverized, and passed through a 400-mesh sieve to obtain apricot shell powder. The apricot shell powder and DES1 treatment agent were added to a container at a mass ratio of 1:10 and stirred at 70 °C for 4 h. Then, pure water at 70 °C was added for dilution, and the mixture was ultrasonically dispersed at a frequency of 30 kHz for 40 min. After filtration, the mixture was continuously washed with pure water at 70 °C until the filtrate was neutral. The filter cake was then placed in a constant temperature oven at 80 °C and dried to constant weight.
[0074] (III) Filtrate treatment The filtrate was dried to constant weight in an oven at 75 °C and placed in a kiln filled with nitrogen atmosphere. The temperature was increased to 1800 °C at a rate of 10 °C / min and held for 3 h to obtain graphitization. After cooling to room temperature, the graphitization and hydrochloric acid (concentration of 10 mol / L) were mixed at a mass ratio of 1:5 and reacted at 80 °C for 1 h. The mixture was then washed with water and filtered until the pH of the filtrate was neutral. The filter cake was then dried to constant weight in an oven at 80 °C to obtain crystallized carbon.
[0075] (IV) Carbonization treatment The filter cake, DES2 treatment agent, and crystallized carbon from step (II) biomass component separation were mixed evenly at a mass ratio of 1:4:0.03. The mixture was then placed in a tube furnace filled with argon gas and heated to 700 °C at a rate of 8 °C / min, held for 1 h, and then further heated to 1300 °C at a rate of 4 °C / min and held for 2 h. After cooling to room temperature, the mixture was ground through a 400-sieve to obtain biomass hard carbon material.
[0076] Example 3 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.
[0077] (I) Preparation of DES1 and DES2 treatment agents Nickel chloride and acrylic acid were added to a container at a molar ratio of 1:4. Water (300% of the sum of the masses of nickel chloride and acrylic acid) was added and the mixture was stirred at 70 °C until clear. The solution was then rotary evaporated to remove free water, yielding DES1 treatment agent.
[0078] Methyltriphenylphosphine bromide, propionamide, and glycerol were added to a container in a molar ratio of 1:3:3 and stirred continuously at 80 °C until clear to obtain DES2 treatment agent.
[0079] (II) Separation of biomass components Walnut shells were dried at 75 °C for 24 h, crushed, pulverized, and passed through a 400-mesh sieve to obtain walnut shell powder. The walnut shell powder and DES1 treatment agent were added to a container at a mass ratio of 1:15 and stirred at 80 °C for 2 h. Then, pure water at 80 °C was added for dilution, and the mixture was ultrasonically dispersed at a frequency of 40 kHz for 20 min. After filtration, the mixture was continuously washed with pure water at 80 °C until the filtrate was neutral. The filter cake was then placed in a constant temperature oven at 90 °C and dried to constant weight.
[0080] (III) Filtrate treatment The filtrate was dried to constant weight in an oven at 80 °C and placed in a kiln filled with nitrogen atmosphere. The temperature was increased to 2000 °C at a rate of 10 °C / min and held for 1 h to obtain graphitization. After cooling to room temperature, the graphitization and hydrochloric acid (concentration of 12 mol / L) were mixed at a mass ratio of 1:4 and reacted at 75 °C for 2 h. The mixture was then washed with water and filtered until the pH of the filtrate was neutral. The filter cake was then dried to constant weight in an oven at 80 °C to obtain crystallized carbon.
[0081] (IV) Carbonization treatment The filter cake, DES2 treatment agent, and crystallized carbon from the biomass component separation in step (II) were mixed evenly at a mass ratio of 1:5:0.03. The mixture was then placed in a tube furnace filled with nitrogen and heated to 600 °C at a rate of 8 °C / min, holding for 2 h. Subsequently, the temperature was increased to 1300 °C at a rate of 7 °C / min and held for 1 h. After cooling to room temperature, the mixture was ground through a 400-sieve to obtain biomass hard carbon material.
[0082] Example 4 This embodiment describes a method for preparing biomass hard carbon material, which includes the following steps.
[0083] (I) Preparation of DES1 and DES2 treatment agents Ferric chloride and benzoic acid were added to a container at a molar ratio of 1:1. Water (containing 100% of the sum of the masses of ferric chloride and benzoic acid) was added and the mixture was stirred at 50°C until clear. The solution was then rotary evaporated to remove free water, yielding the DES1 treatment agent.
[0084] Methyltriphenylphosphine bromide, formamide, and ethylene glycol were added to a container in a molar ratio of 1:1:2 and stirred continuously at 60°C until clear to obtain DES2 treatment agent.
[0085] (II) Separation of biomass components Coconut shells were dried at 95 °C for 12 h, crushed, pulverized, and passed through a 400-mesh sieve to obtain coconut shell powder. The coconut shell powder and DES1 treatment agent were added to a container at a mass ratio of 1:5 and stirred at 60 °C for 7 h. Then, pure water at 60 °C was added for dilution, and the mixture was ultrasonically dispersed at a frequency of 20 kHz for 60 min. After filtration, the mixture was continuously washed with pure water at 60 °C until the filtrate was neutral. The filter cake was then placed in a constant temperature oven at 85 °C and dried to constant weight.
[0086] (III) Filtrate treatment The filtrate was dried to constant weight in an oven at 85 °C and placed in a kiln filled with nitrogen atmosphere. The temperature was increased to 1600 °C at a rate of 5 °C / min and held for 5 h to obtain graphitization. After cooling to room temperature, the graphitization and hydrochloric acid (concentration of 8 mol / L) were mixed at a mass ratio of 1:6 and reacted at 60 °C for 6 h. The mixture was then washed with water and filtered until the pH of the filtrate was neutral. The filter cake was then dried to constant weight in an oven at 85 °C to obtain crystallized carbon.
[0087] (IV) Carbonization treatment The filter cake, DES2 treatment agent, and crystallized carbon from the biomass component separation in step (II) were mixed evenly at a mass ratio of 1:2:0.01, and then placed in a tube furnace filled with nitrogen. The temperature was increased to 1200 ℃ at a rate of 5 ℃ / min and held for 2 h. After cooling to room temperature, the mixture was ground through a 400-sieve to obtain biomass hard carbon material.
[0088] Comparative Example 1 This comparative example illustrates a method for preparing a biomass hard carbon material, which includes the following steps.
[0089] Coconut shells were dried at 95 °C for 12 h, crushed, pulverized, and passed through a 400-mesh sieve to obtain coconut shell powder. The coconut shell powder was placed in a tube furnace filled with nitrogen and heated to 500 °C at a rate of 5 °C / min, held at that temperature for 4 h, and then further heated to 1200 °C at a rate of 5 °C / min and held for 2 h. After cooling to room temperature, it was ground and passed through a 400-mesh sieve to obtain biomass hard carbon material.
[0090] Comparative Example 2 This comparative example illustrates a method for preparing a biomass hard carbon material, which includes the following steps.
[0091] (I) Preparation of DES1 treatment agent Ferric chloride and benzoic acid were added to a container at a molar ratio of 1:1. Water (containing 100% of the sum of the masses of ferric chloride and benzoic acid) was added and the mixture was stirred at 50 °C until clear. The solution was then rotary evaporated to remove free water, yielding the DES1 treatment agent.
[0092] (II) Separation of biomass components Coconut shells were dried at 95 °C for 12 h, crushed, pulverized, and passed through a 400-mesh sieve to obtain coconut shell powder. The coconut shell powder and DES1 treatment agent were added to a container at a mass ratio of 1:5 and stirred at 60 °C for 7 h. Then, pure water at 60 °C was added for dilution, and the mixture was ultrasonically dispersed at a frequency of 20 kHz for 60 min. After filtration, the mixture was continuously washed with pure water at 60 °C until the filtrate was neutral. The filter cake was then placed in a constant temperature oven at 85 °C and dried to constant weight.
[0093] (III) Filtrate treatment The filtrate was dried to constant weight in an oven at 85 °C and placed in a kiln filled with nitrogen atmosphere. The temperature was increased to 1600 °C at a rate of 5 °C / min and held for 5 h to obtain graphitization. After cooling to room temperature, the graphitization and hydrochloric acid (concentration of 8 mol / L) were mixed at a mass ratio of 1:6 and reacted at 60 °C for 6 h. The mixture was then washed with water and filtered until the pH of the filtrate was neutral. The filter cake was then dried to constant weight in an oven at 85 °C to obtain crystallized carbon.
[0094] (IV) Carbonization treatment The filter cake and crystallized carbon from the biomass component separation in step (II) were mixed evenly at a mass ratio of 1:0.01, and then placed in a tube furnace filled with nitrogen. The temperature was increased to 500 °C at a rate of 5 °C / min and held for 4 h. Subsequently, the temperature was increased to 1200 °C at a rate of 5 °C / min and held for 2 h. After cooling to room temperature, the mixture was ground through a 400-sieve to obtain biomass hard carbon material.
[0095] Comparative Example 3 This comparative example illustrates a method for preparing a biomass hard carbon material, which includes the following steps.
[0096] (I) Preparation of DES2 treatment agent Methyltriphenylphosphine bromide, formamide, and ethylene glycol were added to a container in a molar ratio of 1:1:2 and stirred continuously at 60 °C until clear to obtain DES2 treatment agent.
[0097] (II) Carbonization treatment Coconut shells were dried at 95 °C for 12 h, crushed, pulverized, and sieved through a 400-mesh sieve to obtain coconut shell powder. The coconut shell powder was mixed evenly with DES2 treatment agent at a mass ratio of 1:2, and then placed in a nitrogen-filled tube furnace. The temperature was increased to 500 °C at a rate of 5 °C / min and held for 4 h. Subsequently, the temperature was increased to 1200 °C at a rate of 5 °C / min and held for 2 h. After cooling to room temperature, the mixture was ground and sieved through a 400-mesh sieve to obtain biomass hard carbon material.
[0098] Comparative Example 4 This comparative example illustrates a method for preparing a biomass hard carbon material, which includes the following steps.
[0099] (I) Preparation of DES1 and DES2 treatment agents Ferric chloride and benzoic acid were added to a container at a molar ratio of 1:1. Water (containing 100% of the sum of the masses of ferric chloride and benzoic acid) was added and the mixture was stirred at 50 °C until clear. The solution was then rotary evaporated to remove free water, yielding the DES1 treatment agent.
[0100] Methyltriphenylphosphine bromide, formamide, and ethylene glycol were added to a container in a molar ratio of 1:1:2 and stirred continuously at 60 °C until clear to obtain DES2 treatment agent.
[0101] (II) Separation of biomass components Coconut shells were dried at 95 °C for 12 h, crushed, pulverized, and passed through a 400-mesh sieve to obtain coconut shell powder. The coconut shell powder and DES1 treatment agent were added to a container at a mass ratio of 1:5 and stirred at 60 °C for 7 h. Then, pure water at 60 °C was added for dilution, and the mixture was ultrasonically dispersed at a frequency of 20 kHz for 60 min. After filtration, the mixture was continuously washed with pure water at 60 °C until the filtrate was neutral. The filter cake was then placed in a constant temperature oven at 85 °C and dried to constant weight.
[0102] (III) Carbonization treatment The filter cake from step (II) biomass component separation and the DES2 treatment agent were mixed evenly at a mass ratio of 1:2, and then placed in a tube furnace filled with nitrogen. The temperature was increased to 500 °C at a rate of 5 °C / min and held for 4 h. Subsequently, the temperature was increased to 1200 °C at a rate of 5 °C / min and held for 2 h. After cooling to room temperature, the mixture was ground through a 400-sieve to obtain biomass hard carbon material.
[0103] Comparative Example 5 This comparative example illustrates a method for preparing a biomass hard carbon material, which includes the following steps.
[0104] (I) Preparation of DES1 and DES2 treatment agents Ferric chloride and benzoic acid were added to a container at a molar ratio of 1:1. Water (containing 100% of the sum of the masses of ferric chloride and benzoic acid) was added and the mixture was stirred at 50 °C until clear. The solution was then rotary evaporated to remove free water, yielding the DES1 treatment agent.
[0105] Methyltriphenylphosphine bromide and ethylene glycol were added to a container in a molar ratio of 1:2 and stirred continuously at 60 °C until clear to obtain DES2 treatment agent.
[0106] (II) Separation of biomass components Coconut shells were dried at 95 °C for 12 h, crushed, pulverized, and passed through a 400-mesh sieve to obtain coconut shell powder. The coconut shell powder and DES1 treatment agent were added to a container at a mass ratio of 1:5 and stirred at 60 °C for 7 h. Then, pure water at 60 °C was added for dilution, and the mixture was ultrasonically dispersed at a frequency of 20 kHz for 60 min. After filtration, the mixture was continuously washed with pure water at 60 °C until the filtrate was neutral. The filter cake was then placed in a constant temperature oven at 85 °C and dried to constant weight.
[0107] (III) Filtrate treatment The filtrate was dried to constant weight in an oven at 85 °C and placed in a kiln filled with nitrogen atmosphere. The temperature was increased to 1600 °C at a rate of 5 °C / min and held for 5 h to obtain graphitization. After cooling to room temperature, the graphitization and hydrochloric acid (concentration of 8 mol / L) were mixed at a mass ratio of 1:6 and reacted at 60 °C for 6 h. The mixture was then washed with water and filtered until the pH of the filtrate was neutral. The filter cake was then dried to constant weight in an oven at 85 °C to obtain crystallized carbon.
[0108] (IV) Carbonization treatment The filter cake, DES2 treatment agent, and crystallized carbon from step (II) biomass component separation were mixed evenly at a mass ratio of 1:2:0.01. The mixture was then placed in a tube furnace filled with nitrogen and heated to 500 °C at a rate of 5 °C / min, held for 4 h, and then further heated to 1200 °C at a rate of 5 °C / min and held for 2 h. After cooling to room temperature, the mixture was ground through a 400-sieve to obtain biomass hard carbon material.
[0109] Comparative Example 6 This comparative example illustrates a method for preparing a biomass hard carbon material, which includes the following steps.
[0110] (I) Preparation of DES1 and DES2 treatment agents Ferric chloride and benzoic acid were added to a container at a molar ratio of 1:1. Water (containing 100% of the sum of the masses of ferric chloride and benzoic acid) was added and the mixture was stirred at 50 °C until clear. The solution was then rotary evaporated to remove free water, yielding the DES1 treatment agent.
[0111] Tributylhexylphosphine bromide, formamide, and ethylene glycol were added to a container in a molar ratio of 1:1:2 and stirred continuously at 60 °C until clear to obtain DES2 treatment agent.
[0112] (II) Separation of biomass components Coconut shells were dried at 95 °C for 12 h, crushed, pulverized, and passed through a 400-mesh sieve to obtain coconut shell powder. The coconut shell powder and DES1 treatment agent were added to a container at a mass ratio of 1:5 and stirred at 60 °C for 7 h. Then, pure water at 60 °C was added for dilution, and the mixture was ultrasonically dispersed at a frequency of 20 kHz for 60 min. After filtration, the mixture was continuously washed with pure water at 60 °C until the filtrate was neutral. The filter cake was then placed in a constant temperature oven at 85 °C and dried to constant weight.
[0113] (III) Filtrate treatment The filtrate was dried to constant weight in an oven at 85 °C and placed in a kiln filled with nitrogen atmosphere. The temperature was increased to 1600 °C at a rate of 5 °C / min and held for 5 h to obtain graphitization. After cooling to room temperature, the graphitization and hydrochloric acid (concentration of 8 mol / L) were mixed at a mass ratio of 1:6 and reacted at 60 °C for 6 h. The mixture was then washed with water and filtered until the pH of the filtrate was neutral. The filter cake was then dried to constant weight in an oven at 85 °C to obtain crystallized carbon.
[0114] (IV) Carbonization treatment The filter cake, DES2 treatment agent, and crystallized carbon from step (II) biomass component separation were mixed evenly at a mass ratio of 1:2:0.01. The mixture was then placed in a tube furnace filled with nitrogen and heated to 500 °C at a rate of 5 °C / min, held for 4 h, and then further heated to 1200 °C at a rate of 5 °C / min and held for 2 h. After cooling to room temperature, the mixture was ground through a 400-sieve to obtain biomass hard carbon material.
[0115] The biomass hard carbon materials prepared in Examples 1-4 and Comparative Examples 1-6 were subjected to performance tests under the following conditions, and the test results are shown in Table 1.
[0116] The specific surface area and pore size distribution of the material were tested using the nitrogen adsorption / desorption method and analyzed by the BET method. The 002 and 100 diffraction peak patterns of the carbon material were automatically recorded using a Malvern Panaco X-ray diffractometer, and the diffraction angle (2θ) was read simultaneously. The diffraction was then analyzed according to Bragg's formula. 002 =nλ / 2sin θ to calculate the interlayer spacing d 002 Volume resistivity was obtained using a powder resistivity analyzer. I was obtained using Raman spectroscopy. D / I G The values are: The closed-pore diameter and closed-pore volume were obtained by small-angle X-ray scattering tests and fitting.
[0117] The biomass hard carbon materials prepared in Examples 1-4 and Comparative Examples 1-6 were used as active materials and dispersed with conductive carbon black (SP) and polyvinylidene fluoride (PVDF) in a beaker containing N-methylpyrrolidone (NMP) solvent at a mass ratio of 8:1:1. After heating and stirring to ensure thorough mixing, the slurry was uniformly coated onto copper foil to form electrodes. Subsequently, the electrode sheets were dried under vacuum at 60 °C for 12 h, then rolled and cut into working electrodes with a diameter of 12 mm. CR2025 coin cells (including positive and negative electrode shells, spring contacts, and gaskets) were assembled. The operation was carried out in a glove box filled with inert argon gas, where the water and oxygen content were both less than 0.1 ppm. The assembly was performed in the following order: positive electrode shell, working electrode, electrolyte (1 M NaClO4, PC and FEC volume ratio of 95:5), glass fiber separator, sodium metal sheet, gasket, spring contact, and negative electrode shell. The cells were then encapsulated using a battery encapsulation machine. After encapsulation, the batteries were placed in a 25°C constant temperature chamber for standby. The sodium-ion batteries were tested using a LAND CT 3002A charge-discharge test cabinet within a voltage range of 0~3.0 V to obtain their reversible specific capacity (mAh / g), capacity retention after 1000 cycles at 1C, and capacity retention at 5C / 0.1C.
[0118] Table 1 Performance test results of biomass hard carbon materials prepared in Examples 1-4 and Comparative Examples 1-6
[0119] As shown in Table 1, Examples 1-4 have a certain specific surface area and interlayer spacing d. 002 Larger volume resistivity, lower disorder (I D / I GHigh capacity, abundant closed pores, and high capacity, cycle life, and rate performance in sodium-ion batteries. Comparative Example 2, without DES2 treatment, had a smaller closed pore volume, resulting in lower reversible specific capacity, and uneven dispersion of crystallized carbon led to poor rate performance. Comparative Example 3, without DES1 treatment, could not fundamentally deconstruct the lignin-carbohydrate complex (LCC) cross-linking structure to separate cellulose, hemicellulose, and lignin, thus failing to utilize the characteristics of each component-derived carbon. The resulting hard carbon had dense microcrystalline packing, and its electrochemical performance needed improvement. In Comparative Example 4, the filtrate after DES1 treatment was not graphitized, resulting in incomplete utilization of biomass components and the absence of crystallized carbon, leading to poor conductivity and significantly impacting rate performance. In Comparative Example 5, the DES2 treatment agent did not contain aliphatic amides, preventing deep penetration and anchoring of cellulose, and had a small swelling effect and smaller closed pore volume, resulting in poor electrochemical performance. In Comparative Example 6, the DES2 treatment agent was replaced with tributylhexadecylphosphine bromide, which could not uniformly disperse the crystallized carbon and only served as a phosphorus dopant. Therefore, the conductivity of the material was poor and the electrochemical performance was weakened.
[0120] In addition, comparing Example 1 and Example 4, it can be seen that the biomass hard carbon material prepared by step heating carbonization of filter cake, DES2 treatment agent and crystallized carbon has better performance. This is because the heat preservation treatment at a lower temperature range can slowly thermally decompose the aliphatic amides and alcohols in DES2, and the released gas fully expands the main structure of the material.
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing biomass hard carbon material, characterized in that, Including the following steps: (I) Preparation of DES1 and DES2 treatment agents The hydrogen bond acceptor and hydrogen bond donor are mixed in water, heated until the solution is clear, and then evaporated by rotary evaporation to obtain the DES1 treatment agent. The hydrogen bond acceptor is an inorganic chloride salt, and the hydrogen bond donor is an organic acid. A mixture of methyltriphenylphosphine bromide, an aliphatic amide, and an alcohol is heated until the system becomes clear to obtain DES2 treatment agent; (II) Separation of biomass components The biomass powder and the DES1 treatment agent were mixed, heated and reacted, and then filtered to obtain filtrate and filter cake. (III) Filtrate treatment The filtrate was dried and then catalytically graphitized to obtain graphitized material. The graphitized material was then purified to obtain crystallized carbon. (IV) Carbonization treatment The filter cake, the DES2 treatment agent, and the crystallized carbon are mixed and carbonized, followed by further processing.
2. The method for preparing biomass hard carbon material according to claim 1, characterized in that, Includes at least one of the following features (1) to (19): (1) The hydrogen bond acceptor is selected from at least one of ferric chloride, cobalt chloride, nickel chloride, and copper chloride; (2) The hydrogen bond donor is selected from at least one of benzoic acid, p-toluenesulfonic acid, p-hydroxybenzoic acid, acrylic acid, maleic acid and citric acid; (3) The molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:1~6; (4) The heating temperature in the preparation of DES1 treatment agent is 50~70 ℃; (5) Water is added to the DES1 treatment agent to aid dissolution, and the water is removed by rotary evaporation after the solution is clarified. The water content is 100-300% of the sum of the mass of the hydrogen bond acceptor and the hydrogen bond donor. (6) The aliphatic amide is selected from at least one of formamide, acetamide and propionamide; (7) The alcohols are selected from ethylene glycol and / or glycerol; (8) The molar ratio of the methyltriphenylphosphine bromide, the aliphatic amide, and the alcohol is 1:1~3:2~5; (9) The heating temperature in the preparation of DES2 treatment agent is 60~90 ℃; (10) The mass ratio of the biomass powder to the DES1 treatment agent is 1:5~20; (11) The heating reaction is carried out at a temperature of 50~80 ℃ for 2~8 h; (12) After the heating reaction, hot water at 50~80 °C is added to dilute and ultrasonically dispersed before filtration. The ultrasonic dispersion frequency is 20~40 kHz and the time is 20~60 min. (13) The filter cake from step (II) biomass component separation is washed until neutral and dried at 75~95 °C; (14) The drying temperature is 75~95 ℃; (15) The catalytic graphitization in step (III) filtrate treatment is carried out under an inert atmosphere, wherein the inert atmosphere is selected from nitrogen, argon, helium, neon or xenon; (16) The temperature of catalytic graphitization in step (III) filtrate treatment is 1600~2100 ℃, the heating rate is 1~10℃ / min, and the time is 1~5 h; (17) The mass ratio of the filter cake, the DES2 treatment agent and the crystallized carbon is 1:2~10:0.01~0.06; (18) The carbonization in step (IV) is carried out in an inert atmosphere, which is selected from nitrogen, argon, helium, neon or xenon; (19) The post-processing includes grinding and sieving in sequence.
3. The method for preparing biomass hard carbon material according to claim 1, characterized in that, The biomass powder is obtained by drying, crushing, and sieving fruit shells.
4. The method for preparing biomass hard carbon material according to claim 3, characterized in that, Includes at least one of the following features (i) to (iv): (i) The shell is selected from coconut shell, apricot shell, walnut shell or palm shell; (ii) The drying temperature is 75~95 °C, and the time is 12~24 h; (iii) The crushing process involves coarse crushing followed by fine crushing; (iv) The sieving is a 400-mesh sieve.
5. The method for preparing biomass hard carbon material according to claim 1, characterized in that, The purification process includes acid washing, water washing, and drying of the graphitized material.
6. The method for preparing biomass hard carbon material according to claim 5, characterized in that, Includes at least one of the following features (i) to (iii): (i) The pickling solution used is hydrochloric acid with a concentration of 8~12 mol / L, the mass ratio of the graphite to the hydrochloric acid is 1:4~6, and the pickling temperature is 50~80 ℃ and the time is 2~10 h; (ii) The water washing is performed by water filtration until the pH of the filtrate is neutral; (iii) The drying process involves drying at 75~95 ℃ to constant weight.
7. The method for preparing biomass hard carbon material according to claim 1, characterized in that, The carbonization process in step (IV) employs a stepped heating carbonization method.
8. The method for preparing biomass hard carbon material according to claim 7, characterized in that, First, raise the temperature to 400-700℃ at a rate of 1-10℃ / min and hold for 1-5 hours, then raise the temperature to 1200-1500℃ at a rate of 1-10℃ / min and hold for 1-4 hours.
9. The biomass hard carbon material prepared by the method for preparing biomass hard carbon material according to any one of claims 1 to 8, characterized in that, Includes at least one of the following features (1) to (8): (1) Specific surface area is 5.0~15.0 m² 2 / g; (2)d 002 The wavelength range is 0.370~0.390 nm. (3) The volume resistivity is 0.030~0.050 Ω·cm; (4) I D / I G is 1.80 to 2.00 (5) The reversible gram capacity is 300~330 mAh / g; (6) The capacity retention rate at 5C / 0.1C is 40-60%; (7) The capacity retention rate after 1000 cycles at 1C is 85-95%; (8) The pore size of the closed pore is 0.4~1.8 nm, and the pore volume of the closed pore is 0.1~0.3 cm. 3 / g.
10. A sodium-ion battery, characterized in that, It includes a positive electrode active material, an electrolyte, and the biomass hard carbon material as described in claim 9.